Endoscopic Transnasal Odontoidectomy - Falco, Jeffrey J.; Solares, C. Arturo; Reyes, Camilo (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives The video demonstrates the steps for an endoscopic transnasal approach for resection of the odontoid causing platybasia with basilar invasion.Design The video reviews the clinical presentation, preoperative workup and imaging, patient positioning, technical nuances of the procedure, reconstruction, and clinical outcomes including postoperative imaging.Setting The surgery was performed by a skull base team including otolaryngologists and neurological surgeons at a large regional tertiary care facility.Participants A 59-year-old female with the Chiari I malformation with history of multiple revision cervical spinal surgeries presents with neck pain. Preoperative imaging showed a hypoplastic clivus and platybasia with basilar invasion.Main Outcome Measures The main outcome measures consist of safely removing the odontoid with appropriate closure, reversal of the patient symptoms, and prevention of both operative complications and ventral compression of the brainstem.Results The patient's neck pain improved. There were no intraoperative or postoperative complications besides anterior rightward nasal septal deviation causing unilateral nasal obstruction. A septoplasty was performed to correct the septal deviation 6 months after the initial procedure.Conclusions The endoscopic transnasal approach to the resection of odontoid is a safe and effective treatment to address basilar invasion and ventral compression of the brainstem.The link to the video can be found at: https://youtu.be/m_c3-Vn-l80.
Keywords: odontoidectomy; platybasia; basilar invasion; endoscopic surgery; anterior skull base